Creating Consumer Value From Product Design Through Product Differentiation For Yamaha Nmax Motorcycle Consumers In Pekanbaru: . - Nanda Ria, Bayu Sedih; Wibowo, Yudho; Indriaty, Indriaty (LPPM STMIK Dharmapala Riau, 2025)
The purpose of this study is to determine the effect of product design variables on consumer value variables, to determine the effect of product design variables on product differentiation variables and to determine the effect of product differentiation variables on consumer value variables and to determine the effect of product design on consumer value through product differentiation variables on Yamaha Nmax motorcycle consumers in Pekanbaru. As is known, the demand for Yamaha Nmax in Indonesia can be described as a successful and sustainable market phenomenon, changing the competitive landscape in the premium automatic scooter (skutik) segment with total sales reaching 3 million units in 2025. This research was conducted in Pekanbaru City with a sample of 93 respondents using a purposive sampling method. The criteria for respondents who became the object of the study were Nmax motorcycle users in Pekanbaru. The research method used the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method in the form of an outer model, an inner model, and hypothesis testing. The results of the study indicate that there is no influence of product design variables on product differentiation variables on Nmax Motorcycle consumers in Pekanbaru, seen from the p-value of 0.109 which is greater than 0.05. The results also show that there is an influence of product design on consumer value on Nmax Motorcycle consumers in Pekanbaru with p-value of 0.000 which is smaller than 0.05. A significant influence is also shown from the Product Differentiation Variable on consumer value variables on Nmax Motorcycle consumers in Pekanbaru with p-value of 0.000 which is smaller than 0.05. And so the product differentiation variable successfully mediates the influence of product design variables on consumer value on Nmax Motorcycle consumers in Pekanbaru with p-value of 0.000 which is smaller than 0.05.